Mekanisme Penyebaran Hadis Lemah di Era Digital: Kajian Akun Instagram @hadits_lemah - Ika Hilmiatus Salamah; Muhammad Badrus Sholeh; Muhammad Fadhil Wathani; Rahmatulloh Hadi Negoro; Ahmad Ainul Yaqin (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2025)
The development of social media has made it easier to disseminate religious information, including in the field of hadith. However, this opens up space for the dissemination of weak traditions (dha'if) that are not necessarily authentic. This study aims to explore the pattern of the spread of weak traditions on social media in the Instagram account @Hadits_lemah. The method used is library research with a semiotic approach. This research will reveal three things, first the characteristics of weak traditions in the @Hadits_lemah account, second the pattern of spreading weak traditions in the account and third the strategy to minimize the spread of weak traditions on social media. The result is that the characteristics of weak traditions are varied and contemporary in nature. The pattern of the spread of weak traditions has been identified by the form of presentation of the content and the response of the netizens, while the strategy to minimize it is by collaboration between scholars and experts in Technology to ensure the validity of the traditions that will be practiced by ordinary people in the digital realm.